2021
DOI: 10.1063/5.0058416
|View full text |Cite
|
Sign up to set email alerts
|

Time-synchronized laser-induced fluorescence in the near-field of a 600 Watt Hall thruster

Abstract: We report on the results of an experimental campaign to measure time-varying velocity distributions in the near-field of a low power Hall thruster. We employ a sample-hold technique, enhanced by parallelizing the measurement hardware into several signal processing channels that vastly increases the data acquisition rate. The measurements are applied to study flow field dynamics in a commercial BHT-600 Hall thruster undergoing unforced breathing mode oscillations in the 44-49 kHz range. A very detailed experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For example, in [85] using the LIF method, it was found that a multi-peaked iVDF is present at the outer radius of the plume even at a great distance from the thruster. In [86][87][88], LIF measurements of the iVDF were carried out near the channel, depending on the time. It was found that the a peak of slow ions was periodically formed at a distance of about 15 mm from the channel's exit at the lower half-wave of breathing oscillations.…”
Section: Virtual Cathode and Ivdf Effectsmentioning
confidence: 99%
“…For example, in [85] using the LIF method, it was found that a multi-peaked iVDF is present at the outer radius of the plume even at a great distance from the thruster. In [86][87][88], LIF measurements of the iVDF were carried out near the channel, depending on the time. It was found that the a peak of slow ions was periodically formed at a distance of about 15 mm from the channel's exit at the lower half-wave of breathing oscillations.…”
Section: Virtual Cathode and Ivdf Effectsmentioning
confidence: 99%
“…Measurements of ion dynamics are also useful for improving understanding of the physics involved in Hall thrusters and observed phenomena such as anomalous electron transport [4][5][6][7][8][9][10]. Since LIF is a well established diagnostic used throughout the electric propulsion community, it is important to be aware of the assumptions involved and to investigate those assumptions when possible [11].…”
Section: Introductionmentioning
confidence: 99%